What Do We Know About the World? Rhetorical and Argumentative Perspectives - Gabrijela Kišiček (Windsor Studies in Argumentation, 2013)
his book consists of selected papers delivered at "First International Conference on Rhetoric in Croatia: the Days of Ivo Škarić" in May, 2012, and subsequently revised for publication. Through a variety of different routes, the papers explore the role of rhetoric and argumentation in various types of public discourse and present interdisciplinary work connecting linguists, phoneticians, philosophers, law experts and communication scientists in the common ground of rhetoric and argumentation.